PROJECT FINANCING IN SLOVAK COMPANIES - Kormancova, Gabriela (European Scientific Journal, ESJ, 2013)
This paper investigates the possible resources of project financing in Slovak companies. More specifically, this paper will focus on the criteria which influence the companies by selection of resources of project financing. In order to establish a better understanding of the this problem, this paper will identify who is responsible for whole selection process of project financial resource to provide some background and depth to the research